PENGEMBANGAN MODEL COMPUTER-BASED E-LEARNING UNTUK MENINGKATKAN KEMAMPUAN HIGH ORDER MATHEMATICAL THINKING SISWA SMA - Dahlan, Jarnawi Afgani; Kusumah, Yaya Sukjaya; Sutarno, Heri (Jurnal Pengajaran MIPA, 2011)
The focus of this research is on the development of mathematics teaching and learning activity which is based on the application of computer software. The aim of research is as follows : 1) to identify some mathematics topics which feasible to be presented by computer-based e-learning, 2) design, develop, and implement computer-based e-learning on mathematics, and 3) analyze the impact of computer-based e-learning in the enhancement of SMA students’ high order mathematical thinking. All activity in this research achieved in 2 phases. In the first phase, the following activities are conducted: analysis theoretically topics which are difficult to be delivered by conventional methods, need too many repetitions, need high accuracy, need high speed process, and can be presented more interestingly. In the second phase, the following activities are conducted: designing, developing, and implementing a number of teaching and research instruments; implementing computer-based elearning on mathematics for SMA students’, and analyzing the impact of computer-based e-learning in the enhancement of SMA students’ high- order mathematical thinking.